Eosinophils may play regionally disparate roles in influencing IgA+ plasma cell numbers during large and small intestinal inflammation. (December 2016) - Forman, Ruth; Bramhall, Michael; Logunova, Larisa; Svensson-Frej, Marcus; Cruickshank, Sheena; Else, Kathryn
Abstract Background Eosinophils are innate immune cells present in the intestine during steady state conditions. An intestinal eosinophilia is a hallmark of many infections and an accumulation of eosinophils is also observed in the intestine during inflammatory disorders. Classically the function of eosinophils has been associated with tissue destruction, due to the release of cytotoxic granule contents. However, recent evidence has demonstrated that the eosinophil plays a more diverse role in the immune system than previously acknowledged, including shaping adaptive immune responses and providing plasma cell survival factors during the steady state. Importantly, it is known that there are regional differences in the underlying immunology of the small and large intestine, but whether there are differences in context of the intestinal eosinophil in the steady state or inflammation is not known. Results Our data demonstrates that there are fewer IgA+ plasma cells in the small intestine of eosinophil-deficient ΔdblGATA-1 mice compared to eosinophil-sufficient wild-type mice, with the difference becoming significant post-infection withToxoplasma gondii . Remarkably, and in complete contrast, the absence of eosinophils in the inflamed large intestine does not impact on IgA+ cell numbers during steady state, and is associated with a significant increase in IgA+ cells post-infection withTrichuris muris compared to wild-type mice. Thus, the intestinal eosinophil appears to be less important in sustaining the IgA+ cell pool in the large intestine compared to the small intestine, and in fact, our data suggests eosinophils play an inhibitory role. The dichotomy in the influence of the eosinophil over small and large intestinal IgA+ cells did not depend on differences in plasma cell growth factors, recruitment potential or proliferation within the different regions of the gastrointestinal tract (GIT). Conclusions We demonstrate for the first time that there are regional differences in the requirement of eosinophils for maintaining IgA+ cells between the large and small intestine, which are more pronounced during inflammation. This is an important step towards further delineation of the enigmatic functions of gut-resident eosinophils.